Evaluation of the effects of enameloplasty and air abrasion on sealant micro-leakage. - Aliasghar Soleymani; Zahra Bahrololoomi; Shahrzad Javadinejadi; Parisa Salehi (Tehran University of Medical Sciences, 2014)
Micro-leakage, one of the major reasons for recurrent decays, may lead to uncontrollable flow of liquids, pulp inflammation and peri-apical pathology. The purpose of this in vitro study was to evaluate micro-leakage of pit and fissure sealants after using three different pit and fissure preparation techniques: 1) acid etching, 2) fissure enameloplasty and acid etching, and 3) air abrasion and acid etching.Sixty-nine extracted sound molars and premolars were randomly divided into three groups (23 samples in each group). Teeth were prepared using one of three occlusal surface treatments. Then the sealant was applied on the occlusal fissures of all teeth. The teeth were thermocycled and stored in normal saline. All teeth were sealed apically and coated with nail varnish and then were immersed in a 2% solution of methylen blue. Two buccolingual sections were made. The surfaces were scored 0 to 3 for the extent of micro-leakage using a stereomicroscope. Data were analyzed by Kruskal- wallis and Dunn procedure.Enameloplasty and acid etching were significantly different regarding micro-leakage (P= 0.016), but no significant difference in micro-leakage was observed between air abrasion and the other methods.Enameloplasty followed by acid etching produced significantly less micro-leakage than the acid etching technique. Air abrasion acid etching was better than the acid etching technique in reducing micro-leakage too.